Video Transmission Technique through Dual Transmission of Visible Light / Non-Audible Sound Communication in VLC System - Han, Doohee; Lee, Kyujin (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this paper, we study the video transmission technique through dual transmission technique which uses visible light communication and non - audible sound communication simultaneously in visible light communication system.Methods/Statistical analysis: In high-speed video and multimedia transmission environments, existing visible light communication(VLC) has a problem in that communication is disconnected when visible light does not reach directly or when a shadow area occurs due to an obstacle. Unlike RF communication, if the line of sight due to direct light is not secured, the communication performance deteriorates sharply. In order to solve such a problem, the non-audible sound communication is transmitted in dual with visible light communication so that communication disruption does not occur when a shadow region due to an obstacle occurs. We also proposed a scheme to improve the overall system through diversity gain.Findings: We proposed the video transmission method through dual transmission technique to improve the data rate and quality via VLC and sound communication. This solves the problem of shadowing of existing visible light communication. We expect that the performance of the entire system will be improved through diversity gain through dual transmission.Improvements/Applications: The dual transmission technique which uses visible light communication and non - audible sound communication system can be applied as fusion technology to various environments such as an IoT network environment requiring a bidirectional network or an indoor small-scale network configuration and a home network configuration.Â Â